PENERAPAN PERLINDUNGAN HUKUM TERHADAP WISATAWAN YANG MENGALAMI KERUGIAN DI OBYEK WISATA (STUDI DI KABUPATEN PURBALINGGA) - Sarsiti Sarsiti; Muhammad Taufiq (Faculty of Law, Universitas Jenderal Soedirman, 2012)
In the era of globalization, the protection of domestic service users and the entreprenuer of domestic tourism is needed. This research concern about the application of legal protection and remedies law for tourist who suffered losses in tourist location. The method used is normative juridical approach. The collection of legal substance done by documentary and then analyzed using method of normative qualitative. Based on this research, the Local Government of Purbalingga have no consider the consumer, as a subject in the tourism industry, because only one tourist location existing regulations, and it was only regulate the formation of regional companies. Application of compensation is only applied to physical accident at the tourist location in, cooperation with PT Jasa Raharja, whereas the loss of non physical/material not regulated yet. Dispute settlement as a result of suffered losses in the tourist location can be done peacefully or adversarially by using BPSK or filling a lawsuit to court. Keywords: legal protection, tourist, losses